2018
DOI: 10.1007/s10826-018-1044-1
|View full text |Cite
|
Sign up to set email alerts
|

Surviving Siblings’ Illnesses, Treatments/Health Services over 13 Months after a Sibling’s Death

Abstract: Two million children experience sibling death annually and have problems that require clinical intervention although few receive such help. Effects on surviving siblings’ mental health has been well documented, however their physical health has not. This study described surviving siblings’ illnesses, treatments/health services at 2, 4, 6, and 13 months post-sibling death. The 132 children (76 girls, 56 boys, M 10.6 years, SD 3.43); 30% Hispanic, 51% Black, 26% White were recruited via hospital ICUs and publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The first 6 months after the sibling's death were problematic for surviving children when 85% of elevated anxiety and 91% of "some" depression occurred. A report of children's morbidity and treatments after sibling death found a similar pattern with most of the children's 207 illnesses and 674 treatments/health services occurring in the first 6 months post-sibling death and again in months 11 through 13 37 . Perhaps this pattern reflects the activities in some cultures and religions at the 6-month post-death milestone 23 .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The first 6 months after the sibling's death were problematic for surviving children when 85% of elevated anxiety and 91% of "some" depression occurred. A report of children's morbidity and treatments after sibling death found a similar pattern with most of the children's 207 illnesses and 674 treatments/health services occurring in the first 6 months post-sibling death and again in months 11 through 13 37 . Perhaps this pattern reflects the activities in some cultures and religions at the 6-month post-death milestone 23 .…”
Section: Discussionmentioning
confidence: 83%
“…Perhaps this pattern reflects the activities in some cultures and religions at the 6-month post-death milestone 23 . The 1-year anniversary of the death is often a very sensitive period for families; in some religions and cultures, this anniversary is marked with many activities in the child's memory 36,37 . The first 6 months after sibling death is also when parents' pattern of morbidity has shown the greatest incidence in acute illnesses, hospitalizations, newly diagnosed chronic conditions and medication changes 38,39 , perhaps further sensitizing children's responses.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these situations likely affect the closeness of the parent-child relationship, making parents less reliable reporters of their child's experiences, emotions, symptoms, and behaviors. Brooten et al, 2018 found that parents reported 207 illnesses and 674 treatments or health services for 132 school-aged children and adolescents in the first 6 months after their sibling's death. In the first year after their sibling's death, Brooten et al, (2019) found that school-aged children and adolescents self-reported higher symptoms of anxiety; their parents characterized them as having more anxiety/depression, withdrawal, somatic complaints, and aggressive behaviors, which varied by child age, sex, and time since sibling death.…”
Section: Children's Responsesmentioning
confidence: 99%
“…A sibling's death can elevate young people's risk of health problems [3][4][5][6][7][8][9][10] and influence their transition to adulthood [11][12][13]. Attesting to how influential siblings are [14,15], a sibling's death can be more consequential for young people than a parent's death, at least in terms of its impact on emotional and behavioral problems [16] and health risks [17].…”
Section: Introductionmentioning
confidence: 99%